(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2024)
Mount Semeru in East Java erupted on December 4, 2021, which resulted in dozens of residents in Lumajang Regency dying and thousands of residents fleeing. The government is programming the rehabilitation of infrastructure and facilities, including reconstructing temporary and permanent housing for refugees. The research location is in the refugee relocation area in Sumbermujur Village, Candipuro District. In post-disaster reconstruction programs, permanent housings are built after temporary housings have been occupied for several months. However, in Lumajang Regency, the government accelerated the construction of permanent housing so that the developer completed the permanent housing earlier than the temporary housing. Two types of residential units were built simultaneously on a plot of site by different developers, so problems arose in combining the different housing types. After conducting literature studies and general observations, the researcher selected five cases for further observation. The criteria and technical specifications for temporary units are stated in Lumajang Regent Regulation Number 1 of 2022. The construction of permanent units uses RISHA technology. The two types of housing are planned to be directly connected in integration. This paper aims to explain the implementation of the construction of temporary and permanent housing and identify problems in combining the two types of housing in one plot. Researchers found four categories of issues, namely: differences in floor height at the connection between two building units, door and window openings that do not function because they meet the wall, two areas of the roof that are not connected properly, and there are gaps in the connection between units.